Distinct habitat selection by freshwater morays in tropical rainforest streams. Issue 2 (14th January 2015) - Ebner, Brendan C.; Fulton, Christopher J.; Donaldson, James A.; Schaffer, Jason
Abstract: Morays occupy unique interstitial habitats and function as key predators in marine ecosystems. Conversely, there is limited understanding of the ecology of Gymnothorax polyuranodon, the lone representative of the family Muraenidae known to reside in freshwater systems. In this study, we used field‐based encounters over a 3‐year period in three short–steep–coastal–streams of the Australian Wet Tropics to find that most G. polyuranodon individuals (74%) occupied pools, with very few individuals observed in run (23%) or riffle (3%) mesohabitats. Moreover, G. polyuranodon positively selected microhabitats of slow flow (<0.05 ms −1 ) and deep water (>80 cm), while avoiding high flows (>0.5 ms −1 ) and shallow water (<40 cm depth). Morays exhibited strong preferences for boulders (73% of the immediate stream bed area occupied relative to 36% availability) with most individuals resting directly underneath large or very large boulders. Collecting and compiling records of this rare and elusive species over the long‐term helped to reveal such habitat specialisation. Future management plans for G. polyuranodon should focus on preserving boulder interstices year‐round and maintaining stream‐sea connectivity to facilitate a diadromous life cycle.